PENGAWASAN KETERTIBAN LALU LINTAS OLEH DINAS PERHUBUNGAN INFORMASI DAN KOMUNIKASI KABUPATEN SIAK (Studi Kasus Jembatan Sultan Syarif Hasyim, Perawang) - Yuli Puspita Wulandari; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The bridge of Sultan Syarif Hasyim is a bridge in Siak, Tualang Perawang that was built in 2010. The Bridge Of Sultan Syarif Hasyim has a beautiful view so that many merchants who sell and also many vehicles stopped at the bridge. it is a violation of traffic signs that are dangerously to the safety of other road users. There are also the car with an overloaded freely passing on this bridge. Based on this, the researchers are interested to review how control by the department of transportation. The concept of the theory used is control, proposed by Brantas 2009 which assesses control based on four indicators, that is: define the standards that will be used for monitoring, measuring performance or achievements, comparing performance or results to standards and determine deviations if any take corrective action, if there is a deviation for the implementation and objectives according to plan. The purpose of this research is to knowng the control by the transportation department of information and communication on the bridge of Sultan Syarif Hasyim, Perawang, as well as any factors that influence it. This research uses a qualitative method with an assessment of descriptive data. In gathering the data the researcher used interview, observation and documentation based on purposive sumpling method and analysis by triangulation techniques. The outcome of this research showed that the control of traffic order that made by the transportation department of information and communication is not as expected, if seen by the number of violations that had done by staff and road users. The department of transportation and the traffic unit should be able to act decisively to these merchants, the road users and the car with an overloaded that violate the rules by gving the punishment and placing it in a trade location and suitable for them to sell. So that the bridge of Sultan Syarif Hasyim, Perawang can be function as should as.Key words: controlling,